All rhodes lead here ebook A novel. - Zapata, Mariana (2024)
New York Times bestselling author and the Queen of Slow Burn Romance Mariana Zapata's fan favorite All Rhodes Lead Here, a story about finding love when you least expect it—now with new exclusive content! The people we lose take a part of us with them...but they leave a part of themselves with us too. Aurora De La Torre, or Ora to her friends, knows moving back to Pagosa Springs, Colorado, a place that was once home and is now full of bittersweet memories of her late mother, isn't going to be easy. Starting your whole life over probably isn't supposed to be. But after breaking up with her longtime, famous musician boyfriend, hiding out in a small town in the mountains might be the perfect remedy for a broken heart. And checking out her landlord who lives across the driveway just might cure it, too. Only Tobias Rhodes didn't rent out the apartment to her, rather it was his teenage son, Amos. Fiercely protective of his family and distrusting of strangers, gruff and grumpy Rhodes initially keeps little miss sunshine Ora at a distance. But over days and weeks, long hikes and fireside chats, Aurora breaks down his walls and soon an unbreakable friendship blossoms into a once-in-a-lifetime love.